EFEKTIVITAS PENGGUNAAN MEDIA PEMBELAJARAN VISUAL GOOGLE EARTH DALAM MENINGKATKAN PEMAHAMAN SISWA PADA MATERI LETAK GEOGRAFIS INDONESIA DI KELAS V - Putri, Aspia Winalda; Rustan, Edhy; Suryani, Lilis (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2025)
Mistakes in media selection result in students being bored in participating in learning activities. Google Earth learning media is used so that researchers create an active and conducive learning atmosphere so that it has an impact on students' understanding of the material. This study aims to determine how the use and effectiveness of Google Earth learning media in improving students' understanding of the material on the geographical location of Indonesia. The method used is an experiment with a pre-experimental research design of the one group pretest-posttest design. The research sample was grade V elementary school students. The results of the study showed that the use of Google Earth visual learning media can create active learning and is able to improve students' understanding of the material on the geographical location of Indonesia. The results of the descriptive analysis obtained an average student score (pretest) of 53,25 with a very low category and an average student score (posttest) of 81,37 which is categorized as high. According to the hypothesis test, it is concluded that Google Earth visual learning media is effective in improving students' understanding of the material on the geographical location of Indonesia.